Numerical and Computational simulation of blood flow on hybrid nanofluid with heat transfer through a stenotic artery: Silver and gold nanoparticles - Hassan Waqas; Umar Farooq; Ali Hassan; Dong Liu; Sobia Noreen; Roa Makki; Muhammad Imran; Mohamed R. Ali (Results in Physics, 2023)
The proposed study aims to examine the numerical modeling of hybrid nanofluid with nanoparticles such as gold and silver across stenotic artery using Computational fluid dynamics (CFD) in COMSOL Multiphysics. Blood is employed as the base fluid in this research investigation. The flow is modeled as an unstable, incompressible, and laminar Newtonian fluid and blood's Newtonian character is suitable at high shear rates. The performance of blood flow was studied to receive pressure, heat, and velocity changes caused by the stenotic artery. Silver and gold nanomaterials were employed in this study. The Computational fluid dynamics (CFD) approach was used to develop an algorithm for mass, velocity, and energy. COMSOL Multiphysics was used to produce a fine element-size mesh. To the knowledge of the researchers, no one has previously tried to obtain medical processes and therapy implications by studying the flow via a deformed porous channel using blood as a base fluid and as nanostructure materials. Indeed, the findings of this study are unique, and the numerical findings have never been reported by any scholar.